Peran Pendamping Dalam Intervensi Pada Orang Dengan HIV/AIDS (ODHA). (UI Scholars Hub, 2018)
People living HIV / AIDS have social problems in various dimensions, especially in the social dimension such as being excluded from the social environment, lacking social support, difficulties in establishing relationships with the social environment, and being not confident with status as himself as a person with HIV. To help people living HIV/AIDS problems in their social dimensions, in Jember Regency there is a Peer Support Group (PSG) of Pelangi which intervenes both with individual and group approaches. In carrying out the intervention, there were social worker who included former People living HIV/AIDS and not The role of social worker of the peer support group is very supportive in helping people living HIV/AIDS to overcome the social problems they face. This study was conducted to determine the various roles of PSG of Pelangi in each stage of intervention in people living HIV at the Vicity Clinic in Balung Hospital, Jember Regency. This study uses qualitative research, with descriptive types, and informant determination techniques with purposive sampling. The results of the study indicate that there are various roles carried out by the social worker of the pelangi peer support group at each stage of intervention in people living HIV/AIDS especially in the social dimension. By maximizing these roles, the social worker of the PSG pelangi assistant managed to intervene well at each stage